When acute interstitial nephritis has systemic involvement: TINU syndrome - Pimentel,Ana (2015)
Tubulointerstitial nephritis is commonly related with the use of medication or the presence of infection. When uveitis precedes, follows or simultaneously occurs, a distinct and rare syndrome develops as part of the systemic illness. The initial investigation of tubulointerstitial and uveitis syndrome should exclude other systemic diseases that affect the eye and kidney. The diagnosis must include histopathological and clinical findings. The clinical course and treatment may rely on immunomodulatory agents. Case: 24-year old obese male admitted with rapidly progressive renal insufficiency without any identified precipitant factor that responded well to intravenous metilprednisolone. Renal biopsy revealed acute tubulointerstitial nephritis. Uveitis appeared when systemic steroids were tapered